Noninvasive Monitoring to Demonstrate Postoperative Differences in Regional Hemodynamics in Newborn Infants With d-Transposition of the Great Arteries and Hypoplastic Left Heart Syndrome. Issue 2 (March 2023) - Sahni, Prateek V; Krishnamurthy, Ganga; Sahni, Rakesh
Background: The adequacy of tissue O2 delivery in infants receiving intensive care is difficult to measure directly. Regional O2 (rSO2 ) and fractional tissue O2 extraction (FTOE), the ratio of O2 consumption to O2 delivery, obtained from newer noninvasive tools, such as near-infrared spectroscopy (INVOS) and microvascular tissue oximetry (T-Stat) can provide important information on the adequacy of tissue oxygenation and aid in managing critically ill infants. Methods: We prospectively evaluated differences in rSO2 and FTOE in 26 infants with hypoplastic left heart syndrome (HLHS) (n = 12) or d-transposition of the great arteries (d-TGA) (n = 14). Continuous noninvasive monitoring of SpO2, heart rate, and perfusion index with pulse oximetry, cerebral-rSO2 and renal-rSO2 with INVOS, and buccal tissue oxygenation using T-Stat were performed during immediate postoperative period for 24 hours. Results: The SpO2 and rSO2 in infants with d-TGA were higher compared with the infants with HLHS at all measured sites (buccal mucosa, cerebral, and renal). Significant regional differences were also observed in FTOE across all infants with the highest at the buccal mucosa tissue level, followed by cerebral and renal measurement sites. As compared with infants with d-TGA, infants with HLHS had higher regional FTOE and heart rate, with a lower arterial O2 content and perfusion index. Conclusions: Our study demonstrates the utility of noninvasive hemodynamic monitoring to assess regional oxygenation and perfusion, as evidenced by significant differences in infants with HLHS and d-TGA, conditions with different circulation physiologies. Such comprehensive monitoring can potentially aid in evaluating treatment strategies aimed at preventing organ damage from O2 insufficiency.